SOSIALISASI TIPS MINUM OBAT YANG BENAR BAGI ANAK SD NEGERI 3 LEBAK GROBOGAN - Gigih Kenanga Sari; Anik Wahyuni (LPPM AN Nuur, 2022)
Background: Community service activities with the theme Tips for Taking Medicine Correctly (TMOB) have been implemented and run smoothly and received positive attention from students at SD N 3 Lebak Grobogan. The students were very enthusiastic, as seen from the participants' curiosity about the material presented by asking many questions to the presenter. The aim of this service is to provide knowledge to the community, especially students at SD 3 N Lebak Grobogan about how to take medicine properly and correctly. Improper use of medication will be very detrimental to society. If people know how to take medicine correctly, there will be no side effects that are detrimental to themselves. Method: Information about the benefits of taking medication properly is provided in the form of educational and outreach activities (counseling) to students at SD Negeri 3 Lebak. Results: improvement in children's values in recognizing good and correct tips for taking medication that is safe and participants can recognize tips for taking medication properly and correctly and know what is prohibited when taking medication. Conclusion: students' awareness about how to take medicine properly at SD Negeri 3 Lebak.